Fecal Macronutrient Composition and Acquired Lipodystrophy in Males Infected with Human Immunodeficiency (HIV) Versus Non-Infected Males. (29th May 2020) - Andreae, Mary; Clark, W Andrew; Sterrett, John; Adkins, James; Moorman, Jonathan
Abstract: Objectives: Many persons with an HIV infection and undergoing treatment with Highly Active Anti-Retroviral Therapy (HAART) still experience weight loss, hyperglycemia, hyperlipidemia, gastrointestinal issues (diarrhea and malabsorption), and ectopic fat-redistribution typical of acquired lipodystrophy. Symptoms include non-alcoholic fatty liver disease (NAFLD) and liver fibrosis. This study aimed to further elucidate the relationship between malabsorption in HIV infected males, the macronutrient content of feces, and the association with anthropometric measurements and NAFLD and liver fibrosis. Methods: This research enrolled fourteen male participants that are HIV infected, and 14 non-infected males that were matched for age and body mass index (BMI). Anthropometric measurements BMI and hip to waist ratio were obtained, along with a liver scan for fatty liver and fibrosis using the ARFI ultrasound technique. A full bowel movement was collected for each participant, a small aliquot was collected for future microbiome analysis and the remainder was freeze-dried and stored at −80 C. Proximate analysis of feces were completed for macronutrient composition. Analyses included bomb calorimetry for total kilocalories, kjeldahl and soxhlet for % crude protein and crude fat, respectively, and fiber analysis for % insoluble, soluble, and total fiber. Results: There were no significant differences found between groups in macronutrient content of the feces. Differences between insoluble and soluble fiber approached statistical significance between groups, with HIV infected males having a greater proportion with P  = 0.080, and 0.072 respectively. Anthropometric data approached statistical significance, with the HIV infected males exhibiting a greater value for liver damage ( P  = 0.060) and hip to waist ratio ( P  = 0.015). Conclusions: Surprisingly, macronutrients differences, especially soxhlet (fat level in feces) and bomb calorimetry (total kcals for fecal dry matter) were similar between HIV and non-infected controls even though HIV participants reported GI symptoms. Future analysis of the microbiome may identify altered community metabolism that could result in GI symptoms despite no evidence from macronutrient analysis. Funding Sources: Seed Grant, Center of Excellence in Inflammation, Infectious Diseases and Immunity, ETSU.